Personal Data of Adolescents in Higher Education: The LGPD and the Use of Digital Media for Teaching Activities and Remote Testing - Thaís Duarte Zappelini; Laurianne-Marie Schippers; Alexandre Pacheco da Silva (Revista Direito GV)
Abstract With the spread of the new Coronavirus, Higher Education Institutions (HEIs) needed to adapt to this reality. The implementation of Emergency Remote Teaching (ERT) in Brazil relied on the experiences of distance education (EaD). Also, there was a significant increase in the use of remote testing tools that rely on monitoring (e-proctoring). This context has generated several concerns regarding the protection of vulnerable data subjects. The main objective of this article is to assess the processing of adolescents’ personal data by HEIs in the context of teaching activities carried out by digital means and the use of remote testing that include the collection of sensitive data. For this purpose, we aim to analyze the protective regime for children and adolescents’ sensitive information in Brazil’s General Personal Data Protection Law (LGPD), the appropriate legal bases for their management, and the best practices to be adopted. As a result, we have concluded that specific consent is not the only legal basis applicable to processing data from minors. However, it represents an important possibility of data management by legal guardians and the protection of underage people. In any case, the principles of necessity and transparency must be part of this choice process.